2005
DOI: 10.1001/jama.294.13.1664
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Pulmonary Artery Catheter in Critically Ill Patients

Abstract: HE PULMONARY ARTERY CATHeter (PAC) is used to diagnose various diseases and physiological states, monitor the progress of critically ill patients, and guide the selection and adjustment of medical therapy. 1 The PAC is often considered a cornerstone of critical care and a hallmark of the intensive care unit (ICU). 2 Approximately 1 million PACs are used annually in the United States. 3 However, despite widespread use of these devices, there are conflicting data about their utility. The majority of nonrandomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
271
0
33

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 716 publications
(307 citation statements)
references
References 30 publications
3
271
0
33
Order By: Relevance
“…Recent examples include the use of PA catheters in the ICU (41,42), the use of certain antiarrhythmic agents in an attempt to prevent sudden cardiac death (43), and the use of selected inotropes and vasodilators in the treatment of congestive heart failure (44). When the results of the current observational study on dialysis-requiring AKI in the ICU are integrated with other observational studies and clinical trials, there is no evidence of the superiority of CRRT over IHD and some evidence to support possible inferiority.…”
Section: Discussionmentioning
confidence: 99%
“…Recent examples include the use of PA catheters in the ICU (41,42), the use of certain antiarrhythmic agents in an attempt to prevent sudden cardiac death (43), and the use of selected inotropes and vasodilators in the treatment of congestive heart failure (44). When the results of the current observational study on dialysis-requiring AKI in the ICU are integrated with other observational studies and clinical trials, there is no evidence of the superiority of CRRT over IHD and some evidence to support possible inferiority.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Several clinical studies have demonstrated that plasma levels of BNP and NT-proBNP are useful biomarkers to evaluate the severity and the prognosis of patients with heart failure. [5][6][7] Evaluation of the left ventricular filling pressure or pulmonary capillary wedge pressure is important, especially in patients with severe heart failure, however, direct hemodynamic measurements by Swan-Ganz catheters have not been regularly performed [8][9][10][11] and it has been often estimated by the plasma levels of ANP, BNP, and NT-proBNP and these peptides demonstrate almost equal values under various treatments for heart failure. [12][13][14][15][16] Because two endogenous natriuretic peptides, ANP and BNP, bind to natriuretic peptide receptors (NPR); NPR-A and NRP-C receptors with a relatively higher selectivity for ANP than BNP, 17,18) plasma levels of BNP may be affected by carperitide (ANP) infusion.…”
mentioning
confidence: 99%
“…A meta-analysis (n ¼ 5,051, 13 randomized controlled trials) showed no benefit in mortality, number of days hospitalized, inotrope exposure, or vasodilator therapy when using a pulmonary arterial catheter for critically ill patients in the ICU. 76 Direct cardiac imaging using TEE frequently can bypass these limitations. 73,74 Several studies suggested TEE may be beneficial in noncardiac surgical patients with hemodynamic instability, explaining its strong endorsement for this setting in recent guidelines.…”
Section: Echocardiography In the Management Of Pheochromocytomamentioning
confidence: 99%